Orodispersible films containing chestnut shell phenolics for buccal delivery: a preclinical approach for oral mucositis prevention - Ferreira, Ana Sofia; Silva, Ana Margarida; Macedo, Catarina; Laveriano-Santos, Emily P.; Lozano-Castellón, Julián; Lamuela-Raventós, Rosa M.; Švarc-Gajíc, Jaroslava; Costa, Paulo C.; Delerue-Matos, Cristina; Rodrigues, Francisca (Frontiers in Medical Technology, 2025)
IntroductionOral mucositis (OM) is a prevalent complication of cancer treatment that causes painful erythematous and ulcerated lesions in oral mucosa. Current treatments lack efficacy, being natural compounds explored as alternatives. Chestnut shells (CS) are rich in (poly)phenols with antioxidant, anti-inflammatory, and antitumor properties. This study aims to develop orodispersible films (OFs) with CS extract as active ingredient to manage OM.MethodsOFs, prepared by solvent casting and incorporating the CS extract, were characterized regarding physicochemical, antioxidant/antiradical, and anticancer properties, as well as bioactive compounds permeation through in vitro and ex vivo buccal models.ResultsOFs revealed excellent features: thickness (125 µm), tensile strength (43.05 MPa), elongation (75.28%), weight (19 mg/cm2), moisture content (4.25%), and disintegration time (20.43 min). Significant antioxidant/antiradical activities were observed (TPC = 37.05 mg GAE/g film; DPPH = 143.42 mg TE/g film; FRAP = 0.142 µmol FSE/g film). LC-ESI-LTQ-Orbitrap-HRMS analysis confirmed the high permeation of sebacic acid, epicatechin, isorhamnetin, protocatechuic acid, and L-tyrosine across both models, while cytotoxicity assays in oral epithelial cell lines (HSC3 and TR146) demonstrated the cytocompatibility.ConclusionCS-OFs offers a promising approach for preventing and treating OM, enhancing efficacy and patient comfort by delivering bioactive compounds directly to the oral mucosa.